Problématique des risques politiques en Afrique - Vadcar, Corinne (Assurances)

(untitled) (HEC Montréal, 1994)
Political risks' market faced many changes during the last years. This is particularly true in the case of coverage on African risks. Paradoxically, only few countries from Africa are off cover. This situation is sometimes due to political, historical or economic reasons: some countries being hydrocarbons' exporters or under adjustment programs. But, more generally, banking and export-credits to Africa are decreasing. Insurers' behaviour is moving in the way of "disengagement". However, the management of political risks cannot be considered as unique. It depends on different factors like insurer's portfolio. This is why all attempt of harmonization will be difficult all the more as political risks is under de-politicization and criteria of underwriting are changing from risk-country to risk-project. But cooperation between export-credit insurers and between banks and insurers are highly desirable given decreasing capacities on insurance/reinsurance markets, marginalization of Africa in international trade and increasing difficulties of Africa in terms of access to private financing. In this context, it is worth to apply new approaches in terms of insurance even if the result will be new roles for banks, insurers and international organizations. This evolution will obviously not occur without African counterparts.